Three-dimensional fabrication of engineered bone with human bio-derived bone scaffolds in a rotating wall vessel bioreactor. - Song, K; Liu, T; Cui, Z; Li, X; Ma, X (2008)
Bone tissue engineering has emerged as a promising strategy in the effort to regenerate and repair diseased or damaged bone. The bioreactor, within which engineered bone tissue is cultured, plays a key role in the development of engineered bone graphs. In this work, the potentials of the rotating wall vessel bioreactor (RWVB) and the human bio-derived bone scaffolds (BDBS) for 3D bone culture are evaluated. The osteoblasts isolated from the cranium of neonatal Sprague-Dawley (SD) rat of 3 days old were expanded firstly with microcarrier suspension culture in a RWVB. After the assessment of the biological functions of the expanded cells by histomorphometry, the cells were seeded at 2 x 10(6) and 1 x 10(6) cells/mL, respectively, onto the 3D human BDBS and cultured for 3 weeks in the RWVB. The cells metabolism and nutrient concentration were monitored in the whole culture processes. The structure of the harvested bone tissues was observed with optical microscope and scanning electron microscope (SEM). The biological properties of the engineered bone were detected by alkaline phosphatase (ALP) expression and alizarin red staining to visualize the newly formed bone. Acridine orange/ethidium bromide (AO/EB) double fluorescence staining was used to analyze the cell activity. For a comparative study, cell seeded constructs were also cultured in static conditions. The results indicate that the bone grafts cultured in RWVB with two different seeded cell densities grew well, and the cell number expanded in RWVB was five times as that in T-flask and spinner flask. There were significantly more collagen fibers mineralized nodules and new osteoid tissue formed than those in T-flask and spinner flask. It also demonstrated that with the stress stimulation inside the fluid in the RWVB, the ALP expression could be increased; the formation of mineralized nodules can be accelerated.